2019
DOI: 10.1590/1980-549720190002.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Valores de referência para exames laboratoriais de colesterol, hemoglobina glicosilada e creatinina da população adulta brasileira

Abstract: RESUMO: Introdução: Este artigo teve o objetivo de estimar valores de referência de exames laboratoriais de colesterol, hemoglobina glicosilada e creatinina para a população adulta brasileira. Métodos: Estudo descritivo realizado com os dados laboratoriais da Pesquisa Nacional de Saúde (PNS). Foram coletadas amostras de sangue e urina em subamostra da PNS constituída de 8.952 indivíduos de 18 anos ou mais. Para determinar os valores de referência, aplicaram-se critérios de exclusão, como a presença de doen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In turn, in the case of the LDL variable, it is important to highlight the association with the participants' gender. In Brazil, for example, there is data from comprehensive research that found women to be more vulnerable to higher levels for this marker (28) .…”
Section: At Higher Doses and Intervention Periods Researchersmentioning
confidence: 99%
“…In turn, in the case of the LDL variable, it is important to highlight the association with the participants' gender. In Brazil, for example, there is data from comprehensive research that found women to be more vulnerable to higher levels for this marker (28) .…”
Section: At Higher Doses and Intervention Periods Researchersmentioning
confidence: 99%
“…Since liposomal amphotericin B is the formulation of choice for the treatment and secondary prophylaxis of VL in patients with AIDS and interacts with serum lipoproteins in vitro and in the rabbit model, influencing the drug tissue concentration [11], the hypothesis that human lipids might be involved with liposomal amphotericin B activity against Leishmania was investigated. All measured lipids were low in patients with AIDS and VL, regardless of whether they relapsed [25]. This profile is distinct from those of patients with VL or AIDS, taken separately.…”
Section: Discussionmentioning
confidence: 64%
“…According to Branco et al ( 17 ), the % of body fat between 28.8 and 35.7 is considered normal in the Brazilian population. ( 19 ) Reference values biochemical tests Szwarcwald et al ( 19 ). –: no reference value.…”
Section: Resultsmentioning
confidence: 99%